Konsep Muka Dalam Serial Netflix Stranger Things - Rima Zafira Akbari (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This research analyzes the concepts of positive face and negative face in the dialogues of the Netflix series Stranger Things. The research aims to describe the forms of positive and negative face that are used in figures communication interactions. The research applied qualitative descriptive method and Brown and Levinson’s (1987) theory of face and Yule (1996). The datum was collected from dialogues in several season series of Stranger Things and were analyzed based on the framework of face concepts. The results reveal that positive face is more dominant than negative face, as the relationships among characters are rooted in friendship, solidarity, loyalty, and emotional bonds. Positive face is expressed through attitudes such as optimism, concern, emphasis on shared identity, exaggerated interest, humor, and avoiding disagreement. Conversely, negative face shows in the use of hedges, expressions of gratitude, offering choices to the interlocutor, changing the subject, apologizing, and exhibiting pessimism. This research shows that the use of face concepts reflect the importance of communication in sustaining solidarity, cooperation, and emotional support, especially during dangerous and emotionally stressful situations.